Social Support Networks, Coping and Positive Aging Among the Community-Dwelling Elderly in Hong Kong - Liu, Susu (Springer Nature Singapore : Imprint: Springer, 2019)
The dramatically increasing aging population of Hong Kong has elicited new risks and opportunities to facilitate a positive life for older adults. This book offers a holistic review of gerontological theories and literature, and constructs a conceptual framework of social support networks, coping and positive aging. In light of the implications of the convoy model of social support to depict an indigenous landscape of positive aging in Hong Kong, this is one of the very few empirical studies that adopts both quantitative research and qualitative research. The research consisted of a pilot study of in-depth interviews with 16 older Hong Kong Chinese and a main study surveying 393 older members of District Elderly Community Center. The results of the study indicate that family and peer support constitute the mainstay of support networks of the elderly, and that family and peer support are associated with positive aging. Moreover, the study shows that it is the depth of emotional closeness, namely, close interaction and intimacy with social partners that makes the greatest contribution to positive aging. Additionally, problem coping and emotion coping are found to mediate the relationship between social support networks and positive aging. There is potential in bringing more domestic helpers into elderly care and improving the service quality such that the goal of Aging in Place can be promoted in Hong Kong. Intended for researchers in social work, gerontology and positive psychology, it is also essential reading for graduates and social work professionals interested in this area. This book makes a valuable contribution to social gerontological research among Hong Kong older adults and the promotion of wellbeing in the elderly via the construct of positive aging in the culture of Chinese society.